Оптимізація параметрів та конструктивних рішень апаратів для теплової обробки харчових продуктів - Самойчук, Кирило Олегович; Samoichuk, Kyryl; Тітова, Олена Анатоліївна; Titova, Olena; Дьомін, Олександр Анатолійович; Domin, Oleksandr; Дмитревський, Дмитро В’ячеславович; Dmytrevskyi, Dmytro (Запоріжжя: ТДАТУ, 2025)
UA: У статті розглядаються проблеми оптимізації параметрів та конструктивних рішень апаратів для термічної обробки харчових продуктів. Проаналізовано сучасні тенденції розвитку обладнання, зокрема підвищення енергоефективності, забезпечення рівномірності теплопередачі та дотримання санітарно-гігі-єнічних вимог. Визначено основні проблеми традиційних конструкцій, серед яких – нерівномірний нагрів продукту, висока енергоємність та утворення відкладень на поверхнях теплообміну. Розглянуто сучасні підходи до вирішення цих проблем, зокрема використання обчислювальної гідродинаміки, методу скінчен-них елементів, багатокритеріальної оптимізації та використання інноваційних матеріалів. Аналіз дає змогу виявити перспективні напрями вдосконалення апаратів, інтеграції інноваційних технологій та підвищення ефективності термічної обробки, що забезпечує поліпшення якості продукції, зниження енергоспоживання та підвищення конкурентоспроможності харчових підприємств. /// EN: The article highlights the current issues of optimizing parameters and design solutions for food thermal processing equipment, which play a crucial role in increasing the efficiency of production processes in the food industry. An analysis of modern trends in equipment development is presented, with special attention given to improving energy efficiency, ensuring uniform heat transfer, and strictly meeting sanitary and hygienic standards. The main drawbacks of traditional thermal equipment designs are outlined, including uneven temperature distribution within working volumes, high energy consumption of processes, and the formation of deposits on heat exchange surfaces, which complicate operation and reduce equipment durability. It is shown that overcoming these limitations requires the implementation of innovative approaches to the design, calculation, and construction of equipment. The potential of computational fluid dynamics for modeling coolant flows and predicting heat and mass transfer processes is considered, as well as the finite element method for analyzing the stress-strain state of structures, and multi-criteria optimization, which makes it possible to combine the requirements of energy efficiency, productivity, and reliability. Particular attention is paid to the prospects of using advanced materials with enhanced thermal conductivity and corrosion resistance, capable of reducing deposits and extending service life. The generalization of the analysis makes it possible to identify key directions for improving food thermal processing equipment, which include the integration of innovative technologies, reduction of energy consumption, and enhancement of technological flexibility. This, in turn, contributes to improving the quality of final products, increasing the economic efficiency of production, and strengthening the competitive position of food enterprises in both domestic and international markets.
Optimization of parameters and design solutions of devices for the heat processing of food products
Keywords: теплова обробка; оптимізація апаратів; енергоефективність; CFD; FEM; інноваційні мате-ріали; багатокритеріальна оптимізація; санітарно-гігієнічні вимоги; харчова безпечність; рівномірність нагріву; heat treatment; apparatus optimization; energy efficiency; innovative materials; multi-criteria optimization; sanitary and hygienic requirements; heating uniformity; food safety